2015
DOI: 10.1118/1.4928144
|View full text |Cite
|
Sign up to set email alerts
|

Compressed‐sensing‐based content‐driven hierarchical reconstruction: Theory and application to C‐arm cone‐beam tomography

Abstract: A flexible compressed-sensing-based algorithmic approach is proposed that is able to accommodate for a wide range of constraints. It is successfully applied to C-arm CBCT images that may not be so well approximated by piecewise constant functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Before, obesity has been considered to be an important cause of coronary heart disease. Studies of Langet et al [14] showed that the inflammatory cells produced by various adipose tissues in the human body changed the function of vascular wall endothelial cells, smoothed muscle tissue, and other cells, resulting in the production of atherosclerotic plaque. Based on the theory of compressed sensing, an optimized reconstruction algorithm was constructed firstly, and the algorithm in the diagnosis of the CT image was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before, obesity has been considered to be an important cause of coronary heart disease. Studies of Langet et al [14] showed that the inflammatory cells produced by various adipose tissues in the human body changed the function of vascular wall endothelial cells, smoothed muscle tissue, and other cells, resulting in the production of atherosclerotic plaque. Based on the theory of compressed sensing, an optimized reconstruction algorithm was constructed firstly, and the algorithm in the diagnosis of the CT image was used.…”
Section: Discussionmentioning
confidence: 99%
“…Compressed sensing (CS) is a new theory different from traditional data processing technologies. With the major theoretical breakthrough made by Donoho in 2006 as a hallmark, compressed sensing theory is marching forward continuously [14]. Its basic theoretical system equation is as follows:…”
Section: E Optimized Compressed Sensing Ct Reconstructionmentioning
confidence: 99%
“…Quadratic forms like scriptQnfalse(ffalse) have already been used with sparsity‐enforcing regularizers to correct for angular subsampling and cone‐beam artifacts. Dual‐rotation, however, is aimed at avoiding the need for a strong a priori like sparsity.…”
Section: Methodsmentioning
confidence: 99%
“…A high frequency Moire pattern is visible when using H * (right image) due to the redundancy introduced by oversampling the projection, while the backprojected view remains uniform with K (left image). An estimate of x is obtained by adopting a sparse inducing formulation, reminiscent from the literature on compressive sensing [9,25,26,30,36]. We solve the penalized least squares problem (10) with g = ρ W • 1 , W ∈ R N ×N being the orthogonal Symlet 2 wavelet transform on 2 resolution levels, and ρ > 0 the associated regularization parameter.…”
Section: Numerical Experimentsmentioning
confidence: 99%